IMPROVING THE PHYSICAL FITNESS OF CADETS OF THE ACADEMY OF THE REPUBLIC OF UZBEKISTAN WITH THE HELP OF CROSSFIT TOOLS AND METHODS - Mirzakulov Akrom Gafurjanovich (Proximus Journal Publishing, 2024)
The widespread introduction of physical culture and sports into the lifestyle of a modern person is currently acquiring important social and hygienic significance. This is due to the peculiarities of modern civilization, which creates conditions for a sharp restriction of motor activity in everyday life and work – the most important stimulator of vital processes. The main value of physical culture and sports, especially in our time, is the creation of the ideal of a decent lifestyle and the image of a harmoniously developed person. Our physical education system has a set of preventive and hygienic measures aimed at the comprehensive development and maintenance of physical performance and motor activity of people for many years to come.
Keywords: crossfit; physical culture; sport